Modern day problems: The moderating effect of technology anxiety in understanding customer purchasing intention towards over-the-top entertainment platforms as an effect of attitude towards piracy and acceptance of choice overload - Adamos, Gabriel John L. (Animo Repository, 2023)
Opportunities for the over-the-top platforms rose as need for entertainment increased during COVID-19. This study identifies customer response to OTT based on attitude-towards-piracy (AP), choice-overload (CO), and technology-anxiety (TA). No studies combine those variables with purchase-intention (PI); and Filipino OTT users are under-researched respondents. Six hypotheses are proposed: The effect of AP and CO to PI separately, with and without moderator TA; and combined effect of AP and CO to PI, with and without moderator TA. A descriptive-correlational-causal design, surveying 100 NCR-based, 1-month long, OTT users, aged 18-35, through purposive sampling, is followed. The effect of AP to PI was insignificant because PI is independent from ethics; CO leads to PI because choice availability entices customers; AP and CO on PI was insignificant because choosing OTT is difficult when it can be free; TA moderates AP on PI because anxious leechers subscribe out of fear; TA moderates CO on PI because technologically-anxious subscribers have decision fatigue; and TA moderates AP and CO on PI because anxious leechers with decision fatigue want to subscribe. OTT platforms are recommended to hire curators alongside AI algorithms, introduce custom-subscription plans, one-genre marketing, and source-recipient leeching discount to compete against piracy by utilizing CO and TA.